Analysis of Volatile Organic Compounds, Antioxidant, Tyrosinase Inhibitory, and Antimicrobial Activities of Essential Oils from Citronella Grass and Kaffir Lime - Phewphong, Sunti; Roschat, Wuttichai; Jandaruang, Jinda; Leelatam, Tappagorn; Arthan, Supakorn; Poomsuk, Nattawee; Thammayod, Aekkaphon; Maneerat, Bunterm; Namthaisong, Aschara; Siriwong, Khatcharin; Promarak, Vinich (Trends in Sciences, 2025)
This research investigates the volatile organic compounds (VOCs), antioxidant properties, and antimicrobial effects of essential oils from citronella grass and kaffir lime, aiming to assess their potential as natural alternatives to synthetic chemicals in community products. Essential oils were extracted using a prototype distiller, yielding 1.67 % (v/w) from citronella grass and 2.36 % (v/w) from kaffir lime. The chemical compositions were analyzed using gas chromatography-mass spectrometry (GC-MS) and nuclear magnetic resonance (NMR). Antioxidant activities were assessed through assays for 2,2-diphenyl-1-picrylhydrazyl radicals (DPPH•), 2,2’-azino-bis(3-ethylbenzothiazoline-6-sulfonic acid radicals (ABTS•+), and ferric reducing antioxidant power (FRAP). Tyrosinase inhibition and antimicrobial activity were evaluated, with molecular docking studies supporting the findings. Major components in citronella grass oil included geraniol (35.99 % w/w), geranyl acetate (10.73 % w/w), α-citral (7.34 % w/w), and β-citral (5.72 % w/w), while kaffir lime oil contained D-limonene (20.72 % w/w) and (-)-β-pinene (20.19 % w/w). Antioxidant assays revealed lower free radical scavenging activities for both oils compared to Trolox, attributed to their non-polar nature. Citronella grass oil exhibited superior free radical scavenging, due to its molecular structure and electron-donating groups. Tyrosinase inhibition assays showed kaffir lime oil was more effective (IC50 = 195.68 µg/mL) than citronella grass oil (IC50 = 380.45 µg/mL), likely due to smaller, ring-structured molecules. These observations are supported by molecular docking studies. Antibacterial tests demonstrated higher potency of citronella grass oil over kaffir lime oil and clindamycin, with its smaller molecular size enhancing bacterial cell wall interactions. Stability tests revealed that citronella grass oil was initially more effective against Staphylococcus aureus but its activity declined by 45 % on the 2nd day, while still outperforming kaffir lime oil. Essential oils with smaller, simpler molecules provide rapid action but may lose effectiveness over time, whereas complex molecules offer stable, long-term inhibition. Both citronella grass and kaffir lime oils show potential as natural alternatives to synthetic chemicals and can be utilized in products such as soaps, creams, lotions, and disinfectants. HIGHLIGHTS Essential oil yields: 1.67 % (v/w) citronella, 2.36 % (v/w) kaffir lime; key components: Geraniol, citrals, D-limonene, β-pinene. Citronella oil had higher antioxidant activity than both oils and Trolox. Kaffir lime oil (IC50 = 195.68 µg/mL) was more effective in tyrosinase inhibition than citronella (IC50 = 380.45 µg/mL). Citronella oil showed superior antibacterial activity compared to kaffir lime and clindamycin. Both oils are valuable in natural products like soaps, creams, lotions, and repellents. GRAPHICAL ABSTRACT